1982
DOI: 10.1097/00000658-198202000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the First Endoscopic Procedure in the Differential Diagnosis of Gastric Lesions

Abstract: The accuracy of endoscopy and directed biopsy in the differential diagnosis of gastric lesions was evaluated by comparing the diagnoses of one endoscopic procedure (endoscopy and multiple directed biopsies) with the definitive diagnoses in 333 patients. The overall endoscopic and bioptic accuracy rate for all patients amounted to 98.8%. Separate accuracy rates of endoscopy alone and biopsy were 86.5% and 94.9%, respectively. The reliability of endoscopy was similar in the diagnosis of malignant and benign lesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 4 publications
1
13
0
Order By: Relevance
“…The sensitivity and specificity of the potential malignant endoscopic characteristics were high. The sensitivity of endoscopic suspicion in combination with histologic examination at the first endoscopy was 100 %, which is in line with the 99 % accuracy of endoscopic characteristics in combination with histologic analysis found by others [11,17]. Also, Manas et al [9] discovered only one malignancy among the 279 second-look endoscopies performed in their prospective study.…”
Section: Discussionsupporting
confidence: 73%
“…The sensitivity and specificity of the potential malignant endoscopic characteristics were high. The sensitivity of endoscopic suspicion in combination with histologic examination at the first endoscopy was 100 %, which is in line with the 99 % accuracy of endoscopic characteristics in combination with histologic analysis found by others [11,17]. Also, Manas et al [9] discovered only one malignancy among the 279 second-look endoscopies performed in their prospective study.…”
Section: Discussionsupporting
confidence: 73%
“…Upper digestive tract endoscopy is the gold standard for the diagnosis of gastric tumors and has improved the accuracy of diagnosis [8]. When combined with biopsy and brush cytology, endoscopy has an overall sensitivity of 95%–98% in the detection of gastric cancer [9], [10]. Unfortunately, endoscopy is not accepted by all patients, as it is rather invasive and traumatic.…”
Section: Introductionmentioning
confidence: 99%
“…A few previous studies showed that overall endoscopic and bioptic accuracy rates are very high at 97.4 to 98.8% (19,20). Thus, initial gastroscopy has higher diagnostic accuracy than that of the second-look gastroscopy.…”
Section: Discussionmentioning
confidence: 98%